Diffusion of excellence: evaluating a system to identify, replicate, and spread promising innovative practices across the Veterans health administration - Jackson, George L.; Fix, Gemmae M.; White, Brandolyn S.; Cutrona, Sarah L.; Reardon, Caitlin M.; Damschroder, Laura J.; Burns, Madison; DeLaughter, Kathryn; Opra Widerquist, Marilla A.; Arasim, Maria; Lindquist, Jennifer; Gifford, Allen L.; et al. (Frontiers in Health Services, 2024)
Healthcare systems have the goal of providing equitable access to high quality healthcare services that make the best use of available resources. This is particularly challenging in rural areas. This paper summarizes results of a long-term, mixed-methods implementation evaluation of the Veterans Health Administration's (VHA's) Diffusion of Excellence (DoE) program. DoE has the goal of identifying, replicating, and spreading innovative clinical and administrative practices across the largest fully integrated healthcare delivery system in the United States. DoE has used a Shark Tank model to identify more than 3,000 innovations, and 88 innovations have been designated DoE Promising Practices and further replicated. Successful practices have been adopted over 1,400 times in the VHA with the help of DoE staff, training, and web resources. The present paper describes key aspects of the reach, effectiveness, adoption, implementation, and maintenance of the DoE program. This work demonstrates the utility of having a long-term, embedded evaluation team collaborating with DoE. DoE and its evaluation process offer an important example of a large learning health care system. DoE has matured and evolved over the course of more than seven years, including maintaining momentum during the COVID-19 pandemic.